Hubris in leadership: A peril of unbridled intuition?. (February 2015) - Claxton, Guy; Owen, David; Sadler-Smith, Eugene
Research attests to the perils of hubristic leadership in politics, the military and business organizations, however whilst researchers have identified hubris' correspondences with personality disorders and various organizational and individual level factors, the cognitive and affective antecedents of hubris have been largely overlooked. In this paper we argue that intuition, existing as it does at the nexus of cognition and affect, is a central factor and that when intuition becomes misunderstood, unchecked or unbridled within the 'cognitive economy' of a powerful individual hubristic behaviour is more likely to appear. In what follows we will: review the concepts of hubris, Hubris Syndrome and intuition; propose intuition as an overlooked cognitive and affective source of leaders' hubris; discuss the relationship between unbridled intuition and hubris; suggest how the perils of hubristic leadership stemming from unbridled intuition might be avoided or mitigated.